Encouraging Economic Growth Through Islamic Financial Principles in Indonesia - Patriandi Nuswantoro (Westscience Press, 2024)
This qualitative study explores the potential of promoting economic growth through Islamic finance principles in Indonesia. Through interviews with key stakeholders, including policymakers, representatives from Islamic financial institutions, and Shariah scholars, perceptions, challenges, opportunities, and strategies related to Islamic finance are examined. The findings highlight the optimism about the role of Islamic finance in driving economic growth, alongside challenges such as regulatory constraints, lack of awareness, and limited product innovation. Strategies for enhancing regulatory frameworks, promoting financial literacy, and fostering innovation and collaboration are discussed as avenues for unlocking the full potential of Islamic finance in Indonesia.